WHAT DO LAW STUDENTS NEED AND WHAT PROBLEMS THEY EXPERIENCED IN LEARNING ENGLISH? INSIGHT FROM STUDENTS AND ALUMNI - Hardiana, Tusi; Rosayanti, Novinda (Premise: Journal of English Education and Applied Linguistics, 2023)
Many scholars addressed how English was essential to master in many fields. However, few scholars addressed what content of English was required by significant law students. This article, therefore, proposes a little investigation: the problem encountered by law students in mastering English, the basic skills, and materials considered fundamental to be taught in the learning process. Descriptive quantitative was applied to gather the data. Seven-four second-semester students and alums majoring in Law were taken as samples. The researchers collected the data and analyzed them using Microsoft Excel. The findings of the first research question revealed that listening was the most difficult skill to be perceived by the students majoring in Law. Moreover, the finding of the second research question claimed that speaking was assumed as the most necessary skill to be taught. Furthermore, formal and informal English languages were expected to be involved in English learning materials. By looking at the findings of this research, the practitioners can be used as a reference for the betterment of designing materials for Law students. The study implies that students frequently encounter the essential skills and materials to be taught.